Inhibition effect of small interfering RNA of connective tissue growth factor on the expression of extracellular matrix molecules in cultured human renal proximal tubular cells. (March 2014) - Liu, Yuyuan; Li, Weiwei; Liu, Hong; Peng, Youming; Yang, Qiu; Xiao, Li; Liu, Yinghong; Liu, Fuyou
Abstract Objective: In this study, we investigated the effect of small interfering RNA (siRNA) of connective tissue growth factor (CTGF) by pRetro-Super (PRS) retrovirus vector on the expression of CTGF and related extracellular matrix molecules in human renal proximal tubular cells (HKCs) induced by high glucose, to provide help for renal tubulointerstitial fibrosis therapy. Methods: HKCs were exposed to d-glucose to observe their dose and time effect, while the mannitol as osmotic control. Retrovirus producing CTGF siRNA were constructed from the inverted oligonucleotides and transferred into packaging cell line PT67 with lipofectamine, and the virus supernatant was used to infect HKC. The expression of CTGF, fibronectin (FN) and collagen-type I (col1) were measured by semi-quantitative RT-PCR and Western blot. Results: In response to high glucose, CTGF expression in HKCs was increased in a dose- and time-dependent manner, whereas the increase did not occur in the osmotic control. Introduction of PRS-CTGF-siRNA resulted in the significant reduction of CTGF, FN, col1 mRNA (p < 0.01, respectively) and CTGF, col1 protein (p < 0.05, respectively) expression, while PRS void vector group did not have these effects (p > 0.05). Conclusions: CTGF siRNA therapy can effectively reduce the levels of CTGF, FN and col1 induced by high glucose in cultured HKCs, which suggested that it may be a potential therapeutic strategy to prevent the renal interstitial fibrosis in the future.